Analyses of phytochemical constituents in Justicia gendarussa extract: a mini review / Nur Hazaratul Safia Fisol ... [et al.] - Safia Fisol, Nur Hazaratul; Hassan Cheong, Nur Dayana; Mohamed, Emida; Haron, Norhisham; Camalxaman, Siti Nazrina; Rambely, Azlin Sham (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Justicia gendarussa is a plant from the Acanthaceae family with numerous medicinal benefits. Several studies have reported the phytochemical compounds of J. gendarussa extract however, the method used for detection of the chemical constituents have not been reviewed. Hence, the purpose of this review is to look at various methods used in the detection of chemical constituents of the J. gendarussa extract. Previous research were collected from Google Scholar which resulted in thirtyseven articles related to J. gendarussa and detection of its phytochemical constituents. From the review, detection methods involved were qualitative screening, thin layer chromatography, liquid chromatography, and gas chromatography. While phytochemical compounds detected were alkaloid, anthraquinons, betacyanin, linoleic acid, oleic acid, apigenin, kaempferol, naringenin, vitexin, Gendarusin A, glycosides, anthocyanin, tannins, carotenoids, saponins, steroids and carbohydrates. Results of analysis demonstrated that every method has its advantages and disadvantages. Therefore, this review will help researchers in choosing the best and most suitable method for phytochemical analysis depending on their need and interest.